Development, Stability, and In Vitro/In Vivo Studies of Volatile Oil Pickering Emulsion Stabilized by Modified Amber - Maomao Zhu; Zhonghuan Qu; Yanjun Yang; Ruyu Shi; Bing Yang; Yajun Shi; Junbo Zou; Xiaobin Jia (MDPI AG, 2024)
Volatile oil stabilization strategies based on encapsulation with a large number of excipients limit further applications. The primary objective of this study is to improve the stability of volatile oils using Pickering emulsion (PE) stabilized by Chinese medicinal powder based on the principle of "integrating drug and excipient". Modified amber was acquired through surface modification, and a stable oil-in-water PE loaded with Acorus tatarinowii volatile oil (ATVO) was constructed from modified amber. The stability, including the peroxide value (PV), malondialdehyde (MDA) content, and the content and composition of volatile components in modified amber-PE (MAPE) under intense light exposure, was analyzed deeply. In addition, the in vitro release and pharmacokinetics of MAPE and ATVO were investigated. The results demonstrate that the PV and MDA content in MAPE were significantly lower than in free ATVO, and the content and composition of volatile components in MAPE were closer to those in untreated ATVO. The release kinetics of β-asarone and α-asarone in MAPE demonstrated rapid and higher release, and pharmacokinetic studies show that MAPE has better bioavailability. This research provides a distinctive Chinese medicine solution to address the vaporization of volatile oil in solid formulations.